Students’ Numeracy Activities in Group Discussions: A Positioning Theory Perspective - Azizah, Nurul; Faizah, Siti; Pristiani, Riska (Lucerna : Jurnal Riset Pendidikan dan Pembelajaran, 2026)
Unequal participation in mathematics group discussions often restricts students’ opportunities to engage in meaningful numeracy practices and develop conceptual understanding collaboratively. While previous studies have widely examined cooperative learning and classroom interaction, limited research has investigated numeracy activities through the lens of positioning theory. This study aimed to describe fifth-grade students’ numeracy activities in group discussions based on their positioning as experts, facilitators, and novices. A qualitative descriptive approach was employed involving 25 fifth-grade students from a public elementary school in Malang, Indonesia. Data were collected through numeracy tests, classroom observations, and semi-structured interviews to explore students’ interaction patterns and participation during mathematical discussions. The findings revealed that expert-positioned students tended to dominate calculation procedures, strategy selection, and answer validation, which often reduced opportunities for novice students to actively construct understanding. However, groups characterized by active facilitator roles demonstrated more balanced interaction patterns, as novice students were encouraged to explain reasoning, ask questions, and contribute ideas during discussions. These interaction dynamics created more inclusive learning environments and supported meaningful numeracy engagement among group members. The study highlights the importance of teachers designing structured collaborative discussions that distribute participation more equitably and encourage dialogic interaction to strengthen students’ numeracy learning experiences.